Prospective study on mortality predictors in acute exacerbations of chronic obstructive pulmonary disease - Bam, Niraj; Khadka, Sandeep; Shrestha, Bibek; Ayer, Nabin (Journal of Chitwan Medical College, 2025)
Introduction: Acute exacerbations of chronic obstructive pulmonary disease are frequent causes of hospitalization and mortality. Early identification of patients at risk of poor outcomes enables timely interventions and improves management. Method: A prospective observational study was conducted at Tribhuvan University Teaching Hospital, Nepal from 20 Jul 2023 to 20 Jul 2024, among patients admitted with acute exacerbations of chronic obstructive pulmonary disease. Ethical approval was obtained. Demographic, clinical, and laboratory data were collected at admission. Patients were categorised into low, medium, high risk by DECAF score. Data were analysed using IBM SPSS. Categorical data were analysed using the Chi-square test/Fisher’s exact test. Continuous data were analysed using the independent t-test/ANOVA. Multiple logistic regression analysis was conducted to identify predictors of mortality. A p< 0.05 was considered statistically significant. Result: Among 111 participants, majority (56%) were low risk, 1/3rd (33.3%) intermediate risk, and minority (16.2%) high risk, with a mortality of 0%, 10.81%, and 38.89% respectively, p=0.001. Higher DECAF scores were significantly associated with the need for mechanical ventilation (p=0.008) and longer hospital stay (p<0.0001). The scoring system demonstrated good predictive ability for in-hospital mortality with an area under the curve of 0.806. Conclusion: The DECAF score serves as a practical bedside tool to predict mortality, need for ventilation, and hospital stay in patients with acute exacerbations of chronic obstructive pulmonary disease. It aids clinical decision-making and resource allocation. Larger multicentre studies with extended follow-up are recommended to confirm its wider applicability and prognostic accuracy.